A Large Strains Finite Element Multiscale Approach. Issue 1 (2nd January 2016) - Molina, A.J. Carneiro; Curiel-Sosa, J. L.
Abstract : A novel formulation for multiscale finite element analysis of multiphase solids undergoing large strains is proposed in this paper. Within the described homogenization technique no constitutive assumptions are made at the macrolevel. A crucial aspects of the approach is the modeling of antiperiodic traction on the boundary of the representative volume element, condensation technique and the formulation performed on a deformation-driven context whereby the macroscopic deformation gradient is prescribed. Numerical tests on solids with voids demonstrated the robustness of the technique.